Rapid Review of Men's Behavior Change Programs. (December 2021) - O'Connor, Amanda; Morris, Heather; Panayiotidis, Anastasia; Cooke, Victoria; Skouteris, Helen
Family violence is recognized as the violence toward a family member that is threatening, coercive, controlling, dominating, and causes people to fear for their safety and well-being; this complex problem primarily affects women and children. In order to enhance women and children's safety, Men's Behavior Change Programs (MBCPs) aim to achieve change in perpetrators' violent behaviors, by making men accountable and responsible for their actions. The objective of this rapid review was to examine MBCP content, implementation, and the impact on participant and family outcomes. Thirteen articles and 10 MBCPs were identified, using PRISMA guidelines, electronic database searches, and an inclusion criteria of English peer-reviewed articles examining MBCPs or domestic violence perpetrator programs with male perpetrators of family/domestic/intimate partner violence as program participants. The findings of this review indicated a limited evidence base of detailed MBCP evaluations. Information relating to program content was included for nine MBCPs and covered a wide range of topics. None of the articles examined the links between men's accountability and responsibility to the safety and well-being of women and children. Also, none of the articles included assessments of integrity of program delivery, system processes, or evaluations based on program logics. Positive changes were reported for MBCP participants, including communication, parenting, interpersonal relationships, aggression, abuse, responsibility for behavior, self-awareness power and control tactics, empathy, skills development, cognitive beliefs, behavior control, and abusiveness patterns. A whole family approach was utilized by some of the programs and one article reported on family outcomes.